Ways to resolve the Kashmir conflict (Journal of Oriental Studies, 2016)
Тhe dispute between India and Pakistan is continuing from Independence till present time. To date, this conflict is a long dispute in the world. Considering several options to resolve the conflict.
Keywords: Kashmir problem; the Indo-Pakistani conflict